2020
DOI: 10.1002/hyp.13713
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of plant litter in the topsoil on the soil detachment process by overland flow in typical grasslands of the Loess Plateau, China

Abstract: Plant litter can be incorporated into topsoil by a natural process, affecting the soil erosion process. This is a widespread phenomenon in erosion-prone areas. This study was conducted to investigate the effect of litter incorporation on the process of soil detachment on the Loess Plateau, China. Four common plant litters (Bothriochloa ischaemum L. Keng., Artemisia sacrorum Ledeb., Setaria viridis L. Beauv., and Artemisia capillaris Thunb.) were collected, then incorporated into the silt loam soil at five rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The deposition of clay and silt particles from the upstream riverbank during submersion and surface runoff from high elevations during exposure may partly explain this phenomenon (Li, Bao, et al, 2019; Wang, Zhang, Yang, et al, 2018). In addition, the significantly high organic matter at the 150–170 m elevation segment may be explained by the high aboveground and underground biomasses possibly corresponding to the enhanced accumulation of plant litter in the soil, the deposition of which is conducive to the accumulation of soil organic matter (Liu, Li, et al, 2020). The significantly high MWD at the 160–170 m elevation segment may be explained by the high amounts of organic matter and roots (Table 2; Kořenková & Matúš, 2015; Bachmann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The deposition of clay and silt particles from the upstream riverbank during submersion and surface runoff from high elevations during exposure may partly explain this phenomenon (Li, Bao, et al, 2019; Wang, Zhang, Yang, et al, 2018). In addition, the significantly high organic matter at the 150–170 m elevation segment may be explained by the high aboveground and underground biomasses possibly corresponding to the enhanced accumulation of plant litter in the soil, the deposition of which is conducive to the accumulation of soil organic matter (Liu, Li, et al, 2020). The significantly high MWD at the 160–170 m elevation segment may be explained by the high amounts of organic matter and roots (Table 2; Kořenková & Matúš, 2015; Bachmann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although floor litter layer can intercept a small portion of rainfall, it plays a vital role in the regional soil and water conservation. Because it can block the direct contact between rainfall and topsoil, thus weakening raindrop splashing erosion and soil moisture evaporation and slowing down the surface runoff (Liu, Li, Liu, & Flanagan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (2016) found that rill erodibility decreased exponentially with increasing litter density, whereas soil critical shear stress increased with litter density. Liu et al (2020) also showed that the K r of soil incorporated with plant litter decreased by 32% to 46% whereas its τ c increased by 98% to 193%, compared to bare soil. With the decomposition of litter incorporated within the topsoil layer, the effects of litter on soil erosion decreased gradually (Sun, Zhang, Luan, & Liu, 2016).…”
Section: Introductionmentioning
confidence: 95%